Omron PLC Automation Control System for Souvenir Conveyors - Sari, Mokh. Suseno Aji; Zakaria , Dimas Aji (Universitas Panca Marga, 2023)
Souvenirs are relatively small objects and the price is not expensive, forgifts or purchased as a memento from a place visited, for example from a relative's or relative's wedding. Initially, souvenir products were part of the handicrafts produced by the creativity of the craftsmen who were able to turn worthless objects into attractive handicraft products, and were in great demand by many people, especially tourists. Souvenirs are not only handicrafts for souvenirs from a place, but have penetrated into the industry which are widely used and used in events, activities and ceremonies so that they are mass produced. In everyday life, souvenirs are still using a manual system. PLC system development is relatively easy, has much better resistance, is cheaper, consumes less power, detects errors more easily and quickly, fewer cablingsystems, and easy maintenance. PLCs are widely used in industrial applications such as packaging processes, material handling, automated assembly, etc. PLCs produce an output to control goods counter conveyors. A ladder diagram program that uses the CX Programmer application can be applied as commands in the PLC and produces an output that is used to drive and control the pneumatic control system on souvenirs.